ABI_017: Interview with members of ProKids CI (NGO working in the field of sex education) about sex education and school pregnancies (Health Discourses as Moral Communication? Linguistic Case Studies from Côte d'Ivoire and Cameroon, 2022)
Interview with members of ProKids CI (NGO working in the field of sex education) about sex education and school pregnancies.
Keywords: Communication; Ethics; Women; Pregnancy; Reproductive health; Africa; Teenage pregnancy; Abortion; Contraception; Prevention; Applied ethics; Birth Control; Moral Communication; Côte d'Ivoire; Ivory Coast; Adolescent Pregnancy; Morality